RETRACTED: MicroRNA-34c Inhibits Osteogenic Differentiation and Valvular Interstitial Cell Calcification via STC1-Mediated JNK Pathway in Calcific Aortic Valve Disease - Yang, Lieming; Zhu, Xinyuan; Ni, Yingying; Wu, Dawei; Tian, Yikui; Chen, Zhi; Li, Mingbiao; Zhang, Hao; Liang, Degang (Frontiers in Physiology, 2020)
Calcific aortic valve disease (CAVD), a common heart valve disease, is increasingly prevalent worldwide and causes high morbidity and mortality. Here, we aimed to investigate a possible role for miR-34c in the development of osteogenic differentiation during CAVD and to find out the underlying mechanisms. Valvular interstitial cells (VICs) were isolated from the clinical aortic valve tissue samples of CAVD patients and patients with acute aortic dissection and collected. Then, RT-qPCR was performed to determine miR-34c expression and western blot analysis was applied to confirm the relevant protein expression in these VICs. Dual luciferase reporter gene assay was applied to confirm the relation between miR-34c and STC1. Alkaline phosphatase (ALP) staining and alizarin red staining was performed to further confirm the degree of calcification in these samples. MiR-34c was lowly expressed and STC1 was highly expressed in the CAVD tissues. Furthermore, STC1 was the target of miR-34c and was negatively regulated by miR-34c. Overexpression of miR-34c in VICs was concomitant with suppression of both STC1 expression and phosphorylation level of c-Jun N-terminal kinase (JNK). In addition, significant decrease of bone morphogenetic protein-2 (BMP2) and osteocalcin, as well as the decrease of calcification degree were also observed in VICs with miR-34c overexpressed. Taken together, miR-34c could inhibit osteogenic differentiation and calcification of VICs by suppressing the STC1/JNK signaling pathway in CAVD, making miR-34c a novel therapeutic target for the treatment of CAVD.